Sebaceous carcinoma with apocrine differentiation arising in a known case of basal cell carcinoma: A rare entity - Manisha Ahuja; Shramana Mandal; Meeta Singh; Nita Khurana; Padam Singh Bhandari (Wolters Kluwer Medknow Publications, 2024)
Sebaceous carcinoma is a ra malignant tumor of adnexal origin arising from sebaceous glands. It is most commonly seen arising from the eyelids and head and neck. It is predominantly seen in females with an average age of around 65 years. Apocrine differentiation in sebaceous carcinomas is rare but has been reported in the literature. Here, we present a case of sebaceous carcinoma with apocrine differentiation in a 62-year- old female who was a diagnosed case of basal cell carinoma.